2020
DOI: 10.3386/w26949
|View full text |Cite
|
Sign up to set email alerts
|

How Does Household Spending Respond to an Epidemic? Consumption During the 2020 COVID-19 Pandemic

Abstract: excellent research assistance. This draft is preliminary and comments are welcome. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
350
2
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(394 citation statements)
references
References 0 publications
23
350
2
8
Order By: Relevance
“…In sum, the ndings in Table 1 are supportive evidence that the COVID -19 pandemic had led to a signi cant rise in the poverty levels of households. Consistent with extant literature, while Baker, Farrokhnia, Meyer, Pagel and Yannelis (2020) found that the COVID-19 pandemic had increased the poverty levels of households in terms of decrease in overall household consumption, Van Lancker and Parolin (2020) found that COVID-19 had increased child poverty. At the same time, Sumner, Hoy and Ortiz-Juarez (2020) observed that the adverse effect of COVID-19 on poverty is global.…”
Section: Econometric Estimation Of Effect Of Covid-19 On Poverty and supporting
confidence: 57%
“…In sum, the ndings in Table 1 are supportive evidence that the COVID -19 pandemic had led to a signi cant rise in the poverty levels of households. Consistent with extant literature, while Baker, Farrokhnia, Meyer, Pagel and Yannelis (2020) found that the COVID-19 pandemic had increased the poverty levels of households in terms of decrease in overall household consumption, Van Lancker and Parolin (2020) found that COVID-19 had increased child poverty. At the same time, Sumner, Hoy and Ortiz-Juarez (2020) observed that the adverse effect of COVID-19 on poverty is global.…”
Section: Econometric Estimation Of Effect Of Covid-19 On Poverty and supporting
confidence: 57%
“…1 Coverage in the media and some studies examine partisan heterogeneity in response to COVID-19 with no or few controls for differential risk exposure or costs of social distancing (e.g., Economist 2020; Andersen 2020). Baker et al (2020) use transaction-level data and examine heterogeneity in consumption responses to COVID-19. 2 Pastor and Veronesi (2019) also find that Democrats are more risk averse than Republicans.…”
Section: Introductionmentioning
confidence: 99%
“…The first COVID-19 test in the city was conducted on January 29, 2020, with the first positive result not confirmed until February 23, 2020. Nevertheless, by April 6, 2020, 1 Economists have already begun to analyze many of the questions raised by the pandemic; see, for example, Baker et al (2020), Bergen, Herkenhoff, and Mongey (2020), Harris (2020, andLang, Wang, andYang (2020).…”
Section: Introductionmentioning
confidence: 99%